Evaluation of Faculty Members in the Psychiatry Group of Babol University of Medical Sciences: Viewpoints of Internship Medical Students - Shokufeh Mousavi; Sussan Mouodi; Farzan Kheirkhah; Sanaz Azadfrouz; Alireza Sefidchian; Ali Bijani (Babol University of Medical Sciences, 2014)
BACKGROUND AND OBJECTIVE: To evaluate faculty members, quality of teaching in the universities and higher education centers, one of the most common sources for planning and implementation of educational interventions, is the viewpoints of the students. There is a little information about the evaluation of faculty members in the psychiatric groups of medical universities, therefore this research was performed to assess the internship medical students, opinions about the educational status of faculty members in this group. METHODS: This research is a descriptive- analytic study. All of internship medical students who entered to the psychiatric ward of Babol University of Medical Sciences in the year 2012 were delivered questionnaires to report their opinions about the educational status of this group. In this questionnaire, 25 questions in 5 domains related to evaluation of faculty members were considered. According to the scores, results were extracted. Data analysis was performed by Stata SE software, version8. Chi2, Spearman,s correlation coefficients were used for analysis. FINDINGS: Out of total score, mean score in the domain of active presence of faculty member was 90.38±2.78, in the domain of teaching method was 94.15±2.30, the level of knowledge was 94.75±1.71, in the domain of supervision on the function of students was 93.42±2.96 and in the domain of ethics and behavior of faculty member was 95.13±1.81. CONCLUSION: The attitude of internship medical students in Babol University of Medical Sciences is good about the training of faculty members of the psychiatric group.